2012
DOI: 10.1007/s12192-012-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Nrf-2 overexpression in mesenchymal stem cells reduces oxidative stress-induced apoptosis and cytotoxicity

Abstract: The most prominent capabilities of mesenchymal stem cells (MCSs) which make them promising for therapeutic applications are their capacity to endure and implant in the target tissue. However, the therapeutic applications of these cells are limited due to their early death within the first few days following transplantation. Therefore, to improve cell therapy efficacy, it is necessary to manipulate MSCs to resist severe stresses imposed by microenvironment. In this study, we manipulated MSCs to express a cytopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 48 publications
7
83
0
Order By: Relevance
“…Our group also found that regulating local inflammation in ischemic tissue with sarpogrelate could enhance engrafted AD-MSCs viability and antiapoptotic/proangiogenic efficacy in vivo (7). In addition to microenvironmental regulation, increasing the stem cells' ability to resist local stress, such as local inflammation and oxidative stress, is also crucial for stem cell survival and efficacy (22,37). Therefore, it is imperative to improve the engraftment microenvironment as well as reinforce stem cell biological function to withstand the inhospitable ischemic milieu of the infarcted heart.…”
mentioning
confidence: 70%
“…Our group also found that regulating local inflammation in ischemic tissue with sarpogrelate could enhance engrafted AD-MSCs viability and antiapoptotic/proangiogenic efficacy in vivo (7). In addition to microenvironmental regulation, increasing the stem cells' ability to resist local stress, such as local inflammation and oxidative stress, is also crucial for stem cell survival and efficacy (22,37). Therefore, it is imperative to improve the engraftment microenvironment as well as reinforce stem cell biological function to withstand the inhospitable ischemic milieu of the infarcted heart.…”
mentioning
confidence: 70%
“…Transient overexpression of nuclear factor related (erythroid-derived 2)-like 2 (Nrf2) in MSCs results in increased level of super oxide dismutase (SOD) and heme oxygenase-1 Akt a type of protein kinase; eNOS endogenous Nitric oxide synthesis (HO-1), which protect the cells against apoptosis induced by oxidative stress and hypoxic conditions (Mohammadzadeh et al 2012). Nrf2 is an oxidation/reduction-sensitive transcription factor that plays important role in antioxidant defense (Kensler et al 2007;Lee and Johnson 2004).…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…Despite the lack of enough in vivo tracking evidence to support any of those views, some articles showed new strategies aiming at prolonging the survival of MSCs in an adverse environment. P2 hBM-MSCs genetically-modified to transiently express cytoprotective factors (i.e., heme oxygenase-1 or nuclear factor erythroid-2 related factor 2), by using adenoviral vectors, were able to survive better in hypoxic and oxidative-stress conditions [86,87].…”
Section: Strategies To Increase Mscs Migratory Survival and Prolifermentioning
confidence: 99%